Length and weight relationship bronze featherback (Notopterus notopterus, Pallas 1769) in Sei Gesek Reservoir, Bintan Regency, Riau Island - Susiana Susiana; Dedy Kurniawan; Ulfa Rianti; Rapita Rapita (Sangia Publishing, 2021)
Sei Gesek Reservoir is one of the reservoirs in Bintan Regency. This reservoir was dammed in 2011 which is intended to meet the water needs of Tanjungpinang City. One of the types of fish found in Sei Gesek Reservoir is belida fish (Notopterus notopterus). The purpose of this study was to determine the relationship between length and weight of bronze featherback (N. notopterus) in Sei Gesek Reservoir, Bintan Regency. Sampling was carried out from April to June 2021 based on fishermen's catch areas and fish habitats. The relationship between length and weight of male fish W = 0.0000005L3.5115 and female W = 0.000001L2.9067. The b value obtained for male fish shows positive allometric and female fish shows negative allometric.